Increasing efficiency of three-phase induction motors at power supply from single-phase electrical network - V. V. Kharlamov; Yu. V. Moskalev; V. S. Lysenko (Омский научный вестник)
The article discusses the scheme of inclusion of three-phase induction motor to single-phase electrical network. The scheme provides a symmetrical three-phase voltage system on the stator winding. The purpose of the study is to determine the laws of changing the currents of two reactive elements that provide voltage symmetry depending on the slip of the asynchronous motor. The article presents the calculation expressions for determining the conductivity of reactive elements on the known parameters of the electric machine. As a result of the calculation, it is determined that the current of one reactive element should have a capacitive character in the entire range of the slip of the induction motor, the other-capacitive or inductive.